Put on a happy face : a Broadway memoir - Strouse, Charles (New York : Union Square Press, 2008)
Strouse composed some of the most successful shows in Broadway history (Annie, Bye Bye Birdie, Applause, and Golden Boy); wrote the film score for Bonnie and Clyde as well as the theme song for All in the Family; has been sampled by one of today's biggest rap stars (Jay-Z, in the Grammy-winning Hard Knock Life); and his songs have been sung by musical greats from Frank Sinatra to Ray Charles to Barbra Streisand. Timed to coincide with public celebrations of his 80th birthday, this memoir grants an insider's glimpse of Broadway, Hollywood, and beyond. Strouse relates the behind-the-curtain stories of his remarkable achievements, and tells about the people he's worked with along the way, including Butterfly McQueen, Gower Champion, Sammy Davis Jr., Lauren Bacall, Mel Brooks, Clifford Odets, Warren Beatty, Hal Prince and Carol Burnett.--From publisher description.
Includes index.
Keywords: Strouse, Charles; Composers -- United States -- Biography